The role of activity indicators of redox enzymes in evaluation of cornea and conjunctiva condition in experimental hypothyroidism (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Thyroid diseases rank the second place after diabetes mellitus by disease incidence. In recent years, a large number of hypothyroidism studies have showed structural and functional abnormalities in eye tissues.Purpose. To analyze the activity of lactate dehydrogenase and malate dehydrogenase in tears, cornea and conjunctiva in experimental hypothyroidism.Material and Methods. Experimental studies were performed on rats. All the animals were divided into three groups: I – control group (14 rats), II – study group (14 rats), animals with the initial stage of hypothyroidism, and III – study group (14 rats), animals with the pronounced stage of hypothyroidism. In the tissues of the cornea, conjunctiva, and lacrimal fluid, the activity of lactate dehydrogenase and malate dehydrogenase was determined.Results. The data obtained on the reduction of the activity of lactate dehydrogenase and malate dehydrogenase evidence the deterioration of the intensity of the redox processes in tissues of the anterior eye in experimental hypothyroidism.Conclusions. In experimental hypothyroidism, the activity of LDH and MDH is reduced in the cornea by 29.2% and 23.7%, and by 34.7% and 28.7% in the conjunctiva, respectively. A significant increase in the activity of redox enzymes in the lacrimal fluid was revealed in the course of the pronounced hypothyroidism stage (LDH – by 36.3%, MDH – by 24.6%). At that, the degree of change in LDH activity depends on the stage of hypothyroidism.
Keywords: hypothyroidism; cornea; conjunctiva; lacrimal fluid; lactate dehydrogenase; malate dehydrogenase